Familial Mediterranean Gene (MEFV) Mutation in Parents of Children with Familial Mediterranean Fever: What Are the Exceptions? - Leila Shahbaznejad; Sayed-Reza Raeeskarami; Raheleh Assari; Abbas Shakoori; Hamidreza Azhideh; Yahya Aghighi; Fatemeh Tahghighi; Vahid Ziaee (International Journal of Inflammation)
Objectives. Familial Mediterranean Fever (FMF) is one of the most prevalent periodic fever syndromes; MEFV, the responsible gene for the disease, is in the short arm of chromosome16. In the considerable count of the FMF patients, only one mutation is found in the MEFV and parents, who were the obligatory carriers for that mutation, were asymptomatic. The aim of this study was to evaluate these asymptomatic parents in regard to mutation in MEFV gene and similarity between parents and offspring patients. Methods. In this cross-sectional study, asymptomatic parents of FMF patients enrolled the study were referred to periodic fever clinic or pediatric rheumatology clinic of Tehran University of Medical Sciences. The patients should have at least one mutation in MEFV gene and none of them had any family history of autoinflammatory disease. Twelve mutations in MEFV gene were assessed in the parents by Vienna Lab FMF Strip Assay kit by MAS PCR/Reverse hybridization. Results. Forty-three patients and their parents participated in the study. Sixty-three percent (27) of patients were male. Onset of disease symptoms in 31 patients (72%) was before 4 years of old. Nine (21%) of the patients had homozygote, 16 (37%) compound heterozygote, and 17(40%) heterozygote for MEFV mutation; there was a case of complex alleles mutations (2%). M694V/M694V in 4 patients (9%) was the most homozygote genotype, and M694V/R761H in 4 (9%) and E148Q in 7 (16%) were the most compound heterozygote and heterozygote genotype, respectively. M694V, M680I, and E148Q were the most mutation in the parents. Overall, 41 patients had mutations similar to their parents’ mutation, except 2 whose parents had no mutation, but a patient did. Conclusion. It seems that occurrence of new mutations in offspring is not prevalent among FMF patients and there are other reasons for different clinical presentation in similar mutation carriers. On the other hand, in ethnicities with high prevalence of FMF, new mutation in descendant may occur, infrequently.